A gestão pública da Anatel: uma análise sob o enfoque do public service orientation - Colen, Samuel Pinto (2016)
Since the international crisis of the 1980´s, debates concerning new forms of management have increased. In Brazil, the reform of public administration was the main theme of the government of Fernando Henrique Cardoso, which, among other objectives, sought to draw closer State administration and the modern administration practices of private companies. In this context, Managerialism emerges as an answer to the issues of inefficiency and limited resources faced by the State. However, it is not a hegemonic construction. The last strand, Public Service Orientation, apart from worrying about administrative decentralization, policy effectiveness, service quality and the focus on “citizen/client” need, is strongly supported by the participation of society and the creation of spaces for the promotion of transparency and fostering of social learning, in which the user/client can become citizen and the public interest may cease to be an abstraction. With these considerations, we sought to analyze how the management of Anatel, broken down into internal processes and public policies regulation adheres to the premises of the most complex and plural aspect of Managerialism, that is, Public Service Orientation. Therefore, we sought to analyze if the citizens are active elements in signaling demands and evaluating the performance of the operators, as well as if they are integrated and actively take part in the definition of public policies. The nature of this research is qualitative and, to reach the objective proposed, document research was the methodological procedure used. We verified that Anatel created many forms of communication with the citizen, that is, the instruments to fulfill the criteria of the effectiveness of service, attention to the client/citizen. Moreover, the participation of citizens in the definition of public policies was expected, but it did not operate well in practice, concluding that the management of Anatel does not completely adhere to the premises of the PSO.